School and student characteristics related to primary and secondary school students’ social–emotional functioning - de Bruijn, Anne G. M.; Ehren, Melanie C. M.; Meeter, Martijn; Kortekaas-Rijlaarsdam, Anne Fleur (Frontiers in Education, 2025)
IntroductionA healthy social–emotional functioning is vital for students’ general development and wellbeing. The school environment is a major determinant of social–emotional functioning, yet little is known about school-level and student-level characteristics related to healthy social–emotional functioning. In this study, we examined school-level characteristics (school size, school disadvantage score, urbanization level, and school denomination) and student-level characteristics (grade, secondary school track, participation in a COVID-19-related catch-up program, and measurement moment - during or after COVID-19) as predictors of students’ motivation for school, academic self-concept, social acceptance, and school wellbeing.MethodsIn school year 2020–2021, just after the first Covid-19 outbreak, 3,764 parents of primary school students from 242 Dutch primary schools and 2,545 secondary school students from 62 secondary schools filled out online questionnaires, before and after a Covid-19 related catch-up program was implemented at their school. Reliable and validated questionnaires were used to assess students’ motivation (Intrinsic Motivation Inventory), academic self-concept (Harter Self Perception Profile for Children; Self-Description Questionnaire-II), school wellbeing (Dutch School Questionnaire) and social acceptance (PRIMA Social Acceptance Questionnaire). School characteristics were derived from online databases. Student participation in a catch-up program and measurement moment (before or after the program) were taken into account. Data was analyzed via multilevel General Linear Mixed Models, separately for primary and secondary education.ResultsOf the school-level factors, only school disadvantage score was a significant predictor, specifically for primary school students’ motivation. Of the student-level characteristics, grade and catch-up participation were significant predictors of lower motivation, academic self-concept and school-wellbeing in primary school. In secondary school, students in higher grades had significantly lower motivation and school wellbeing; participants in catch-up program had a significantly lower academic self-concept; and perceived social-acceptance and school wellbeing were significantly lower just after COVID-19.ConclusionSchool-level characteristics only played a minor role in explaining differences in students’ social–emotional functioning. In both primary and secondary education, students in higher grades and participating in catch-up programs scored lower on their social–emotional functioning. Schools should be aware of students in higher grades being at risk for more problems in their social–emotional functioning.